FACTORS INHIBITING THE IMPLEMENTATION OF THE ROAD MAP POLICY FOR BUREAUCRATIC REFORM AT THE INSTANTIONAL LEVEL (Study at the Regional Secretariat of Konawe Regency, Southeast Sulawesi Province) - Reski Melyana Melamba (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Reforming the Indonesian bureaucracy is a long-term agenda that continues to be the focus of every government. Bureaucratic reform policy is a process to change processes, public bureaucratic procedures and the attitudes and behavior of bureaucrats to achieve bureaucratic effectiveness and national development goals (Quah, 2022). The bureaucratic reform agenda in Konawe Regency has been going on for 8 (eight) years. During these eight years, dynamics and complexity have colored the steps and movements of bureaucratic reform in the Regional Government of Konawe Regency, Southeast Sulawesi Province. However, unfortunately, until now, or entering the final stage, the implementation is still far from being "successful". Judging from the evaluation results of the implementation of Bureaucratic Reform, it still shows that there is a gap between the current achievements and the expected conditions. This gap can be seen from two sides, namely from the planning side and the implementation side. On the planning side, the 6 context of the 2020-2024 Konawe Regency Bureaucratic Reform Road Map has not yet optimally accelerated good governance, which can be seen from various leverage indicators which are still at a very low level. On the implementation side, there are several obstacles from both internal and external factors, such as the management of Bureaucratic Reform at the OPD level which has not been optimally felt by the community, related to concrete performance for the community, public services, and reducing the practice of Corruption Collusion Nepotism (KKN). Planning and implementation of Bureaucratic Reform is also still being carried out partially by each OPD so that it has not yet focused on national strategic issues and the direction of National Development (Source: Konawe Regency Regional Government Bureaucratic Reform Road Map 2021 to 2025). This research focuses on the factors inhibiting the implementation of the bureaucratic reform road map policy at the Regional Secretariat of Konawe Regency, Southeast Sulawesi Province. The research results show that the factors inhibiting the implementation of the bureaucratic reform road map policy at the Konawe district regional secretariat can be grouped into two categories, namely internal factors and external factors. From the internal side, there are several obstacles, including: limited understanding of the apparatus regarding the road map for bureaucratic reform, lack of relevance of the road map to organizational needs, weak integration of bureaucratic reform programs in planning and budgeting, low commitment from internal stakeholders, and rigidity in bureaucratic governance which is less flexible. Meanwhile, from the external side, the identified inhibiting factors are weak collaboration and coordination with external stakeholders, as well as changes in policies and regulations regarding bureaucratic reform which have not been fully accommodated, synchronized and internalized with regional work plans and strategic plans of regional apparatus organizations referred to in including at the Konawe Regency Regional Secretariat.Keywords:Bureaucratic Reform, Factors Inhibiting Policy Implementation, Road Map, Regional Government